Fintech, Inclusive Growth and Cyber Risks : Focus on the MENAP and CCA Regions - Lukonga, Inutu (IMF Working Papers; Working Paper, 2018)
Financial technology (fintech) is emerging as an innovative way to achieve financial inclusion and the broader objective of inclusive growth. Thus far, fintech in the MENAP and CCA remains below potential with limited impact on financial inclusion. This paper reviews the fintech landscape in the MENAP and CCA regions, identifies the constraints to the growth of fintech and its contribution to inclusive growth and considers policy options to unlock the potential.